Early childhood nutrition concerns, resources and services for Aboriginal families in Victoria - Judith Myers; Sharon Thorpe; Jennifer Browne; Kay Gibbons; Stephanie Brown (Elsevier, 2014)
Abstract Objective: To investigate the child nutrition concerns of Aboriginal families with young children attending Aboriginal health and early childhood services in Victoria; training needs of early childhood practitioners; and sources of nutrition and child health information and advice for Aboriginal families with young children. Method: Qualitative needs assessment involving consultation with Aboriginal parents of young children aged 0-8 years attending Aboriginal health and early childhood services, and early childhood practitioners from Aboriginal health and early childhood services in urban and regional Victoria. Focus groups were conducted with 35 Aboriginal parents and interviews conducted with 45 health and early childhood practitioners. Thematic analysis was used to generate and then refine distinct, internally consistent common themes from the data. Results: The most frequent issues identified were low levels of breastfeeding, inappropriate introduction of solids, reliance on bottles, sweet drinks, and energy‐dense foods, poor oral health and overweight. Concerns about staff training and capacity, and access to maternal and child health services were also common. Conclusion and implication: This study identifies major gaps in service delivery for Aboriginal families with young children and points to the need for a coordinated, culturally responsive systems approach to providing support for breastfeeding and child nutrition advice and support for Aboriginal families, including capacity building for staff, and supportive systems and policy.